2021
DOI: 10.1111/jgh.15589
|View full text |Cite
|
Sign up to set email alerts
|

Liver fibrosis and fatty liver as independent risk factors for cardiovascular disease

Abstract: Background and Aim:The association between liver fibrosis, fatty liver, and cardiovascular disease (CVD) risk is unknown. Hence, this study aimed to investigate the association of liver fibrosis and fatty liver with CVD risk independent of already known CVD risk comorbidities. Methods: This is a prospective study registered with the University Hospital Medical Information Network clinical trial registry (UMIN000036175). Liver fibrosis was assessed by serum fibrosis markers including FIB-4, nonalcoholic fatty l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 43 publications
4
35
0
1
Order By: Relevance
“… 9 , 10 Emerging data from recent studies have suggested that liver stiffness on MRE may be associated with liver-related outcomes. 11 14 Other NITs including the FIB-4 score (fibrosis index based on the 4 factor) and NAFLD Fibrosis Score (NFS) have demonstrated associations with liver-related events and death; 15 17 however, when used alone, they have only modest discriminatory ability. Similarly, vibration-controlled transient elastography (VCTE) is associated with liver-related events among patients with chronic advanced liver disease, 18 but has limited discriminatory ability for liver-related events in patients with less advanced disease.…”
Section: Introductionmentioning
confidence: 99%
“… 9 , 10 Emerging data from recent studies have suggested that liver stiffness on MRE may be associated with liver-related outcomes. 11 14 Other NITs including the FIB-4 score (fibrosis index based on the 4 factor) and NAFLD Fibrosis Score (NFS) have demonstrated associations with liver-related events and death; 15 17 however, when used alone, they have only modest discriminatory ability. Similarly, vibration-controlled transient elastography (VCTE) is associated with liver-related events among patients with chronic advanced liver disease, 18 but has limited discriminatory ability for liver-related events in patients with less advanced disease.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the high CVD risk of lean-MAFLD compared to OW-MAFLD might be due to the in uence of brotic burden. Several previous studies have revealed that advanced liver brosis in patients with FLD is not only a major risk factor for liver cancer or liver-speci c mortality but is also closely related to CVD risk [21,22]. Indeed, in this study, lean-MAFLD with advanced brosis had an increased CVD risk compared to OW-MAFLD without advanced brosis, whereas lean MAFLD without advanced brosis did not.…”
Section: Discussionmentioning
confidence: 43%
“…In another study including 458 patients with biopsy‐proven NAFLD and fibrosis stage 3 or 4, CVD incidence was higher in patients with F3 than those with F4 111 . Among studies investigating the general population, an increased FIB‐4 score was associated with increased risk of CVD 112,113 . In a study that used MRE as a noninvasive marker, CVD incidence was higher in patients with moderate‐advanced fibrosis (MRE: 3.0–4.7 kPa) than those with cirrhosis including decompensation cirrhosis (MRE >4.7 kPa) 97 .…”
Section: Prediction Of Prognosis Using Noninvasive Markersmentioning
confidence: 99%
“…111 Among studies investigating the general population, an increased FIB-4 score was associated with increased risk of CVD. 112,113 In a study that used MRE as a noninvasive marker, CVD incidence was higher in patients with moderate-advanced fibrosis (MRE: 3.0-4.7 kPa) than those with cirrhosis including decompensation cirrhosis (MRE >4.7 kPa). 97 One possible reason for this discrepancy is the distribution of liver fibrosis among studies.…”
Section: Noninvasive Markers and Cardiovascular Eventsmentioning
confidence: 99%